Mechanoelectrical feedback regulates the arrhythmogenic activity of pulmonary veins. Issue 1 (11th August 2006) - Chang, S-L; Chen, Y-C; Chen, Y-J; Wangcharoen, W; Lee, S-H; Lin, C-I; Chen, S-A
Abstract : Background: Atrial fibrillation is commonly associated with dilated pulmonary veins. Stretch has been shown to have mechano-electrical effects. Objective: To investigate whether stretch can increase the arrhythmogenic activity of the pulmonary veins. Methods: The transmembrane action potentials were recorded from rabbit pulmonary veins before and after stretch (100 and 300 mg). Gadolinium and streptomycin (stretch-activated ion channel blockers) were each perfused into the pulmonary veins under a 300-mg stretch. Results: Stretch (0, 100 and 300 mg) force dependently increased the incidence of spontaneous activity (22%, 48% and 83%; p<0.05), mean (standard deviation (SD)) firing rates of spontaneous activity (1.7 (0.2), 2.1 (0.3) and 3 (0.2) Hz; p<0.05) and incidence of early post-depolarisations (9%, 26% and 61%; p<0.05) and delayed post-depolarisations (0%, 4% and 30%; p<0.05) in 23 pulmonary veins. In the seven preparations with spontaneous activity after the 300-mg stretch, gadolinium (1, 3 and 10 μmol/l) decreased the incidence of spontaneous activity by 43%, 29% and 14%, respectively (p<0.05), and decreased the firing rate from 2.9 (0.1) Hz to 0.8 (0.4), 0.3 (0.1) and 0.1 (0.1) Hz, respectively (p<0.05). Streptomycin (10 and 40 μmol/l) decreased the incidence of spontaneous activity by 71% and 29%, respectively (p<0.05), and decreased the firing rate from 2.9 (0.1) Hz to 1.6 (0.4) and 0.5 (0.3) Hz, respectively (p<0.05). Conclusion: Stretch is an important factor in the electrical activity of the pulmonary vein. Stretch-induced arrhythmogenic activity of the pulmonary vein may contribute to the genesis of atrial fibrillation.